As Juntas minhotas de 1808 na reacção à ocupação francesa - Matos, Henrique José Martins (História: revista da Faculdade de Letras da Universidade do Porto, 2018)
The social restoration movement of June 1808 and consequent creation of the “Juntas de Governo”, spread all over the country, but particularly in northern Portugal, are one of the most visible aspects in the political war against the Franco-Spanish occupation of 1807-1808. In this paper, we will analyse the development in the military Province of Minho, the reaction against the foreign occupation, the actions taken by the “Junta de Viana”, and also how the “Junta de Viana” interacted with the other “Juntas de Provincia” and with the “Junta Suprema” created in Porto.